62.3: Invited Paper: Speckle Contrast Reduction in a Blue‐LD Pumped Micro‐Vibrated‐Reflective Phosphor Paper for Lighting Source Applications. Issue 1 (June 2015) - Tu, Shih‐Yu; Lin, Hoang Yan; Lee, Tsung‐Xian
Abstract : We have demonstrated efficient speckle reduction techniques by using both micro‐vibrated and mixing light methods for solid‐state backlighting source applications. A micro‐vibrated‐reflectivephosphor paper is used for speckle suppression and white light generation. A mixing speckle contrast (SC) is defined, and the almost speckle‐free results are achieved.